Doris Lessing Towards a Social Change: A Psychoanalytical Survey of her Select Works - Akhter, Tawhida; Batta, Ajoy (International Journal of Psychosocial Rehabilitation, 2020)
Doris Lessing- the world acknowledged and Nobel Laureate (2007) British writer has her prominent position in the field of literature. She was born in the year 1919 in Persia (Iran) to a British family. Her family further moved to Southern Rhodesia to have their fortune in maize farming. Her father has served in the WWI and was crippled during the war. The family have very harsh memories of the war. Her childhood was of more pain and less pleasure. Being grown up in a country where the racial discrimination is in its heights made her to write about the harsh realities of her own society. During the tenure of her writing she was actively involved in various social and political activities so as to bring a social change. She had wrote more than fifty works including- novels, short-stories, plays, autobiographies and operas. Some of her novels have been made into films. She has seen the harsh realities of her times and through writing she revolted against these menaces in the society. She was actively involved in politics what we can say Communist Party and fought for the racial discrimination in Africa. She was the follower of Marxist Philosophy whose Slogan was to make a free and classless society. They demanded for the discrimination free society and this philosophy or ideology is quite clear in the writings of Doris Lessing. This research paper will bring out the changes that she wants to bring in her society in most of her important works. This research paper will make a critical analysis of the short story from the African Stories volume. The writer’s main motive behind writing these stories is to bring a social change in a society. No one is special and other is inferior only on the basis of colour and Lessing throughout her life fought for this menace.